Is a viable hemp industry in Florida’s future? - Trent Blare; Martha Rivera; Fredy H. Ballen; Zachary Brym (EDIS)
Disease and foreign competition have made many growers question the viability of traditional commodity crops such as tomatoes, citrus, and avocados. Industrial hemp appears to be an attractive alternative, as the 2018 Farm Bill permitted its production. Florida has followed several other states in approving permits in 2020 to allow production of industrial hemp. Markets for industrial hemp products were promising in the first years of production, but market prices started to decline dramatically in 2020 with many growers unable to sell all their product. In this publication, we examine the hemp value chain with a focus on opportunities in the Florida market. Better coordination between regulators, processors, financial institutions, research and Extension services, and the retail sector to build confidence, harmonize policies, and lower transaction costs would help the industry flourish and ensure growers, consumers, and hemp-related enterprises can benefit from this emerging market.